2001
DOI: 10.4049/jimmunol.167.2.1103
|View full text |Cite
|
Sign up to set email alerts
|

Costimulation Blockade, Busulfan, and Bone Marrow Promote Titratable Macrochimerism, Induce Transplantation Tolerance, and Correct Genetic Hemoglobinopathies with Minimal Myelosuppression

Abstract: Mixed hemopoietic chimerism has the potential to correct genetic hemological diseases (sickle cell anemia, thalassemia) and eliminate chronic immunosuppressive therapy following organ transplantation. To date, most strategies require either recipient conditioning (γ-irradiation, depletion of the peripheral immune system) or administration of “mega” doses of bone marrow to facilitate reliable engraftment. Although encouraging, many issues remain that may restrict or prevent clinical application of such strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
213
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(225 citation statements)
references
References 25 publications
10
213
2
Order By: Relevance
“…Bu is typically administered at a dose of 20 mg/kg or higher, with higher levels of chimerism corresponding to dosage increases (6,36,37), as mice are relatively more resistant to Bu than humans. We found that 10 mg/kg Bu was sufficient to deplete LSK progenitors without severely affecting WBM cell numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Bu is typically administered at a dose of 20 mg/kg or higher, with higher levels of chimerism corresponding to dosage increases (6,36,37), as mice are relatively more resistant to Bu than humans. We found that 10 mg/kg Bu was sufficient to deplete LSK progenitors without severely affecting WBM cell numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of regulation is also time dependent, as it declines over time in protocols leading to progressive peripheral clonal deletion [67]. CD4 + [11,68], CD4 + CD25 + [67], CD4 + CD25 − [60], and CD4 + FoxP3 + [70,71] cell populations have all been found to play a regulatory role in various rodent models of transplantation tolerance [70].…”
Section: Regulatory Mechanismsmentioning
confidence: 99%
“…Regulatory (i.e., nondeletional) mechanisms appear to inhibit donor-specific alloreactivity through a series of incompletely defined, cell contact dependent or cytokine-mediated mechanisms [63,64], taking place in secondary lymphoid organs or in the graft [65,66]. The less drastic the recipient conditioning [11,67,68], the more pronounced becomes the contribution of regulation in addition to deletion. Along these lines, regulation is critical in the NHP setting and in clinical trials (see below) in which permanent mixed chimerism (which is a prerequisite for maintaining continuous central deletion) is not achieved [69].…”
Section: Regulatory Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations